2019
DOI: 10.1111/1751-7915.13450
|View full text |Cite
|
Sign up to set email alerts
|

Environmental filtering increases with elevation for the assembly of gut microbiota in wild pikas

Abstract: Summary Despite their important roles in host nutrition, metabolism and adaptability, the knowledge on how the mammalian gut microbial community assemble is relatively scanty, especially regarding the ecological mechanisms that govern microbiota along environmental gradients. To address this, we surveyed the diversity, function and ecological processes of gut microbiota in the wild plateau pika, Ochotona curzoniae, along the elevational gradient from 3106 to 4331 m on ‘the Roof of the World’—Qinghai‐Tibet Plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 97 publications
(139 reference statements)
5
70
3
Order By: Relevance
“…This study revealed that the phyla Firmicutes and Bacteroidetes were the predominant bacteria in the rumen of yaks. The two phyla in the current study were also found to be abundant in the GIT of yaks [1,2,4], sheep [19], goats [20], bovine animals [21], and pikas [11], indicating an ecological and functional role of Firmicutes and Bacteroidetes in the mammalian GIT. Huang and Li (2017) [22] reported that the relative abundance of Firmicutes in yaks was higher than that of Bacteroidetes during grazing.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…This study revealed that the phyla Firmicutes and Bacteroidetes were the predominant bacteria in the rumen of yaks. The two phyla in the current study were also found to be abundant in the GIT of yaks [1,2,4], sheep [19], goats [20], bovine animals [21], and pikas [11], indicating an ecological and functional role of Firmicutes and Bacteroidetes in the mammalian GIT. Huang and Li (2017) [22] reported that the relative abundance of Firmicutes in yaks was higher than that of Bacteroidetes during grazing.…”
Section: Discussionsupporting
confidence: 62%
“…These unique characteristics result in an attractive system explore the adaptation process of yaks to altitudinal gradients. First, because the main characteristics of high altitude areas are low pressure, low oxygen, low temperature, high sunlight, and climate dynamics [ 11 ], the ecological mechanisms associated with rumen microbiota consortium could respond in a different manner compared with those of low altitude yaks. Second, yaks have adapted well to high altitude environments through long-term evolution [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiome data analysis was mainly performed using QIIME Pipeline-Version 1.9.0 ( http://qiime.org/scripts/index.html ) from our Microbiome and Bioinformatics Platform in School of Public Health, Lanzhou University. The detailed analysis methods and procedures were described in our previous reports with slight modification ( 14 17 ). In brief, the original paired-end reads produced by MiSeq sequencer were assembled using the FLASH-1.2.8 software ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the microbiota, bacteria are the most abundant, diverse, and metabolically active species in the rumen [ 7 , 8 ]. The bacterial community in the rumen are linked to various factors, such as animal diet, breed, age health and geographic region [ 9 , 10 ]. Diet is the major determinant of the microbial composition in the rumen [ 11 ].…”
Section: Introductionmentioning
confidence: 99%